Use of Lactate Acid Bacterium, Streptococcus thermophilus and Fish Waste Feces to the Blood Cholesterol Level of Broiler Chicken Lohman Strain - Astuti; Bachrudin, Zaenal; Supadmo (International Journal of Poultry Science, 2014)
This research was conducted to examine whether giving Streptococcus thermophilus bacteria in a force feeding way could reduce the level of cholesterol in broiler chicken blood. The source of Microbe used as the research materials was isolate BAL isolated from fish waste in the fish digestion organ. Fourty male broiler chickens strain Lohmann with 4 week ages produced by PT Multi Breeder Adirama was used in this research. They were divided into five different treatments in which each treatment consisted of 8 chickens taken randomly and raised for 42 days. Data collected was analyzed with variance analysis used one way full random design, then, the data analyzed by using Duncan’s Multiple Range Test (DMRT). Lactate Acid bacteria (BAL) used in this research were freeze drying Streptococcus thermopillus which were taken from Biochemistry Nutrition Laboratory of Faculty of Animal Breeding of Gajah Mada University. Treatment I was as a control (Without BAL). Treatment II used 106 CFU/mL BAL cell. Treatment III used 107 CFU/mL BAL cell. Treatment IV used 108 CFU/mL BAL cell. The result of the research showed that giving lactate acid bacteria, Streptococcus thermophilous, significantly reduced the cholesterol level in broiler chicken blood. The reduce of cholesterol level in the chicken blood seemed affected indirectly by the mechanism of gall saline de-conjugation.